Prevalence and Characteristics of Dental Anomalies in Pediatric Patients at a Dental Hospital in Thailand - Sakulratchata, Ruedee; Wongma, Sasipa; Saenmood, Sita; Rianpingwang, Thunyanut; Chiohanangkun, Sasicha (Asian Health, Science and Technology Reports, 2020)
This retrospective study was performed by collecting data from dental records of 385 pediatric patients who had a complete dental examination and treatment planning at Dental Hospital in Phitsanulok, Thailand, during the period of January 1, 2014 – December 31, 2017. The objective of this study is to evaluate the prevalence and characteristics of the most frequently found dental anomalies. The results show that the prevalence of dental anomaly in pediatric patients is 13.25%. The most prevalent anomalies are congenital missing teeth (34.38%), supernumerary teeth (20.31%), embedded teeth (9.38%), enamel hypoplasia (7.81%), and others (1.56%-6.25%). A chi-square test revealed a significant relationship between child age and dental anomaly (P=0.001), in which dental anomaly prevalence is higher in children age 6-12 than in children age 0-5. No significant relationship existed between dental anomaly and sex, systemic disease, or physiological/psychological disorder (P>0.05). The most common disorder associated with dental anomaly was “cleft lip with cleft palate”, and the most common anomaly associated with that disorder was congenital missing permanent anterior maxillary teeth.